Estimating the association between cigarette and e-cigarette use patterns and SARS-CoV-2 negative conversion time: retrospective online survey in China - Ying Xie; Yinghua Li; Zheng Su; Xueyan Han; Zhao Liu; Zhenxiao Huang; Anqi Cheng; Xinmei Zhou; Jinxuan Li; Rui Qin; Xiaowen Wei; Yi Liu; et al. (BMC Infectious Diseases)
Abstract Background Cigarette smoking has been reported to be associated with SARS-CoV-2 negative conversion, while little is known about the effect of its dual use with e-cigarettes. This study aimed to investigate whether tobacco product use patterns including e-cigarette use were linked with delayed negative conversion of SARS-CoV-2. Methods An online national survey was conducted from January 28 through February 21, 2023, targeting a community-based population in mainland of China after peak waves of the coronavirus disease 2019 (COVID-19). Participants were followed from the onset of COVID-19 symptoms until the negative conversion day or the day of answering the questionnaire as the endpoint of the study. Multi-variable adjusted Cox proportional hazard models were used to compare the negative conversion time of SARS-CoV-2 across different cigarette and e-cigarette use patterns. Results A total of 66,537 participants infected with COVID-19 were enrolled and 13,294 were included in the analyses. During the median duration of 7 days (interquartile range 5 to 10 days), a total of 11,587 (87.2%) had a negative conversion. Compared with never users, current exclusive smokers (multi-variable adjusted HR 0.59, 95% CI 0.48–0.71), current dual users (HR 0.31, 95% CI 0.22–0.44), and previous smokers (HR 0.56, 95% CI 0.37–0.83) took longer to turn negative after 10 days of follow-up. Conclusions Both current exclusive cigarette use and dual use of cigarettes and e-cigarettes were associated with the delayed negative conversion of SARS-CoV-2, which strengthens the importance of smoking and vaping cessation messaging and community-based tobacco control strategies during pandemics like COVID-19 next time.